SPEECH COMMUNICATION IN CLOSE LANGUAGE CONTACTS (American Journal of Pedagogical and Educational Research, 2024)
This article examines modern scientific achievements in the field of the theory of bilingualism, which grew on the basis of language contacts, and also examines the leading aspects of bilingualism - linguistic, psychological, pedagogical.